The Notion Of City In Priestley’s English Journey-Priestley’in English Journey Eserinde Şehir Algısı - Onur Kaya (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Many writers aim to express about their journeys and observations on these journeys. Putting forth his journeys and his observations on the cities he observed, John Boynton Priestley provides his style of perspective on English cities and the urbanization in his work English Journey (1933). It is significant to emphasize the perspective of the author about the cities of England, the notion about the city he features and the observations he puts forth. The author and the motives that lead him to the journey will be emphasized. The trend of traveling within the country and reflecting it on the work will be stated. Space concept will be explained for the analysis of the notion of the city. Literary journalism will be explained. The conditions of the English cities, the approach of the writer towards these cities, his typical notion of city he puts forth in the work will be analyzed. Finally, in the study, Priestley’s approach to early 20th century England, cities and elements he puts forth in the context of notion of the city will be revealed.